ChemInform Abstract: Addressing Challenges in Palladium‐Catalyzed Cross‐Couplings of Aryl Mesylates: Monoarylation of Ketones and Primary Alkyl Amines. Issue 48 (26th November 2013) - Alsabeh, Pamela G.; Stradiotto, Mark
Abstract For the first time examples of enolate α‐arylation employing aryl mesylate coupling partners and amination of inexpensive phenol derivatives with primary aliphatic amines are developed.